Testimony of Lois M. Quinn and John Pawasarat to the U.S. Senate Finance Committee Subcommittee on Social Security and Family Policy - (:unkn) unknown (My University, 1990)
In June 1990 Lois Quinn and John Pawasarat of the Employment and Training Institute testified on the progress of their evaluation of the Wisconsin Learnfare experiment before the Senate Committee on Finance Subcommittee on Social Security and Family Policy. They appeared at the request of the committee chairman, Senator Daniel Patrick Moynihan.
Keywords: Learnfare; AFDC; teenagers; truancy; child abuse; child neglect; welfare policy